Spent Li‐Ion Battery Graphite Turned Into Valuable and Active Catalyst for Electrochemical Oxygen Reduction. Issue 4 (12th January 2021) - Liivand, Kerli; Kazemi, Maryam; Walke, Peter; Mikli, Valdek; Uibu, Mai; Macdonald, Digby D.; Kruusenberg, Ivar
Abstract: Employing Li‐ion batteries (LIBs) in portable electronics has become a necessity in the modern world but, due to the short application time for any given battery (1–3 years), the quantity of spent LIBs (SLIBs) waste is becoming substantial. Herein, a novel strategy for recycling SLIB graphite and reforming it as a valuable catalyst material for electrochemical oxygen reduction reaction was proposed. SLIB graphite has been used as a precursor material for graphite oxide, which was thereafter doped with nitrogen to prepare nitrogen‐doped graphene (NG‐Bat). The prepared NG‐Bat was characterized by various physical characterization methods and the electrochemical properties of the resulting catalyst material were investigated in alkaline media. It was found that NG‐Bat prepared from SLIB had superior physical and electrochemical properties in comparison to commercial nitrogen‐doped graphene. The findings clearly demonstrate the importance of the recycling of SLIB graphite and its great potential to be re‐applied for various applications. Abstract : One man's trash : A novel strategy is proposed to recycle spent Li‐ion battery (SLIB) graphite and reform it as a valuable catalyst material for electrochemical oxygen reduction reaction. Catalyst material prepared from SLIB graphite has superior physical and electrochemical properties in comparison to commercial N‐doped graphene. The findings clearly demonstrate the importance of the recycling of SLIB graphite and its great potential to be re‐applied for various applications.